2017
DOI: 10.17221/86/2017-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant effects of lycopene on bovine sperm survival and oxidative profile following cryopreservation

Abstract: Reactive oxygen species overgeneration as a side effect of semen cryopreservation may lead to lipid peroxidation, protein degradation, DNA fragmentation and cell death, resulting in a decrease of sperm survival and fertilisation ability. Lycopene has been proposed as a potential supplement to semen extenders because of its antioxidant properties. The aim of this study was to evaluate the effects of lycopene on the structural integrity, functional activity and selected oxidative stress parameters of cryopreserv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 33 publications
5
24
0
Order By: Relevance
“…Tvrda, Mackovich [20] suggested that lycopene supplementation to semen extender acts as an In vivo result showed that watermelon in dextrose saline when used as diluent for rooster semen enhanced fertility and hatchability of eggs than undiluted semen and dextrose saline.. This thus corroborates claim by Jimoh and Ayedun [13] that watermelon juice is a potent diluent and can be incorporated as extender constituent in the preservation of semen for optimal performance.…”
Section: Discussionsupporting
confidence: 63%
“…Tvrda, Mackovich [20] suggested that lycopene supplementation to semen extender acts as an In vivo result showed that watermelon in dextrose saline when used as diluent for rooster semen enhanced fertility and hatchability of eggs than undiluted semen and dextrose saline.. This thus corroborates claim by Jimoh and Ayedun [13] that watermelon juice is a potent diluent and can be incorporated as extender constituent in the preservation of semen for optimal performance.…”
Section: Discussionsupporting
confidence: 63%
“…Acrosomal integrity was evaluated using bright field microscopy at 1000× using oil immersion. At least 200 cells per slide were evaluated for the presence or absence of acrosome, and expressed as a percentage rate (Tvrda et al 2017).…”
Section: Acrosomal Integritymentioning
confidence: 99%
“…In more recent studies, lycopene decreased lipid peroxidation of spermatozoa and increased sperm viability and motility [12]. Via antioxidant mechanisms, leptin, carnitine, and lycopene reduced DNA damage during storage of spermatozoa [12] [13] [14]. Natural antioxidants, such as ascorbic acid and α-tocopherol, have produced conflicting results on sperm function post-preservation [7] [8] [15] [16], suggesting there may be an optimal threshold for antioxidant supplementation, and above that threshold, the beneficial effects may not be realized.…”
Section: Introductionmentioning
confidence: 92%
“…Prevention of oxidative stress by supplementation of culture media and cryopreservation extenders with antioxidants has been investigated previously [9] [10] [11]. In more recent studies, lycopene decreased lipid peroxidation of spermatozoa and increased sperm viability and motility [12]. Via antioxidant mechanisms, leptin, carnitine, and lycopene reduced DNA damage during storage of spermatozoa [12] [13] [14].…”
Section: Introductionmentioning
confidence: 99%